Efficient Performance Parameters for Solar Cells - Balo, Figen; Sua, Lutfu S. (wiley, 2023)
Both the number and the capacity of renewable energy applications have significantly increased as a consequence of enhanced awareness and strategies to meet growing requirements for energy. In latest years, therefore, all nations have worked to raise the sustainable energy share among other power generation techniques in order to guarantee energy independency. Energy security concerns, decreasing levels of conventional energy sources, and solar radiation leves are significant determinants the feasibility of installing sun energy technologies. Due to the absence of accessible meteorological information, various models were created to predict sun irradiation concentrations. All the same, these designs rely heavily on the features of climate and environment. For a particular climate region, this paper aims to determine the most proper models. This study is a part of country-wide solar radiation model development effort. In this research, to design the photovoltaic facility for maximal effectiveness under particular circumstances, a simulation software package is used to analyze the region under inquiry using the deterministic models of solar radiation in accordance with the specified climatic circumstances. According to the results obtained, the most suitable equipment for the Ankara province was determined by the AHP method among top 10 confirmed cell and modules worldwide. © 2021 Scrivener Publishing LLC.
Keywords: correlation models; data analysis; panel efficiency; photovoltaic systems; Solar energy